Strategi Pengembangan Pajak Daerah Di Kabupaten Buton Tengah - Rahmawati, Rahmawati; Uddin, Aksar; Andriani, Rinita; Abidin, Zainul (Bahasa Indonesia, 2025)
This research aims to explain the local tax development strategy in Central Buton Regency. This research uses a descriptive method with a qualitative approach. Data was collected using interview, observation and documentation techniques. The results showed that the tax development strategy was carried out both through intensification and extensification. The intensification strategy is carried out through updating and improving data, expanding the revenue base, intensifying collection, increasing supervision, increasing administrative efficiency and reducing collection costs, conducting better planning and utilizing information technology support. Extensification strategies are carried out through the expansion of tax collection and coordination and support with other parties. However, the implementation faces many obstacles. The implementation has not yet achieved the desired intention. This is indicated by the results of tax revenues that have not experienced a significant increase and are still fluctuating. Of the eight types of local taxes levied, Rural and Urban Land and Building Tax, Fees on Acquisition of Land and Building Rights, Billboard Tax and Arts and Entertainment Services Tax are classifiedin the underdeveloped category.